Patient Satisfaction and Quality of Life with Enhanced Recovery Protocols - Li, Debbie; Jensen, Christine C. (Clinics in Colon and Rectal Surgery, 2019)
While studies have demonstrated the benefits of Enhanced Recovery after Surgery (ERAS) programs in reducing length of stay and costs without increasing complications, fewer studies have evaluated patient satisfaction and quality of life (QOL) with enhanced recovery protocols. The aim of this project was to summarize the literature comparing satisfaction and quality of life after colorectal surgery following treatment within an ERAS protocol to standard postoperative care. The available evidence suggests patients suffer no detriment to satisfaction or quality of life with use of ERAS protocols, and may suffer less fatigue and return to activities sooner. Most publications reported no adverse effects on postoperative pain. However, a limited number of studies suggest patients may experience increased early postoperative pain with ERAS pathways, particularly following open colorectal procedures. Future research should focus on potential improvements in ERAS protocols to better manage postoperative pain. Overall, the evidence supports more widespread implementation of ERAS pathways in colorectal surgery.
Keywords: Enhanced Recovery after Surgery; fast track; satisfaction; quality of life; postoperative care